2019
DOI: 10.1159/000499475
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA 3,860-bp Deletion Increases with Aging in the Auditory Nervous System of C57BL/6J Mice

Abstract: <b><i>Background/Aims:</i></b> Mitochondrial DNA (mtDNA) is sensitive to oxidative damage during aging, which can result in mtDNA mutations. A previous study reported that a 3,860-bp mtDNA deletion, similar to a 4,977-bp mtDNA deletion in humans, is also common occurrence in murine tissues, and increases in the brain and liver with aging. However, no previous study evaluated both topics in the murine auditory nervous system. <b><i>Methods:</i></b> We compared mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Interestingly, the 3860-bp deletion of the mitochondrial DNA in mice is closely located to the 4977-bp deletion in humans, and can also be found in various aged tissues. Furthermore, its occurrence increases in the auditory nervous system, in the liver, and in the brain with aging (Du et al 2019a;Zhang et al 2009Zhang et al , 2013. In our study, the 3860-bp CD increased gradually in the Dgal-treated CBM compared to increased levels observed in the control CBM.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Interestingly, the 3860-bp deletion of the mitochondrial DNA in mice is closely located to the 4977-bp deletion in humans, and can also be found in various aged tissues. Furthermore, its occurrence increases in the auditory nervous system, in the liver, and in the brain with aging (Du et al 2019a;Zhang et al 2009Zhang et al , 2013. In our study, the 3860-bp CD increased gradually in the Dgal-treated CBM compared to increased levels observed in the control CBM.…”
Section: Discussionsupporting
confidence: 47%
“…The SYBR green RT-PCR assay was used to evaluate the relative quantity of mitochondrial DNA with a 3860-bp deletion. This common deletion (CD) increases with aging in the auditory system of mice (Du et al 2019a), as reported previously (Zhang et al 2009(Zhang et al , 2013. Briefly, total DNA was extracted using a Genomic DNA Isolation kit (Tiangen Biotech, Beijing, China) and the DNA concentration of each specimen was measured (GeneQuant II, RNA/DNA calculator, GE Healthcare, Parramatta, Australia).…”
Section: Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 93%
“…Relatively few studies have examined energy metabolism in the central auditory system during aging. For example, aging-related accumulation of reactive oxygen species or reduction of reactive oxygen species-scavenging enzymes, such as superoxide dismutase, as well as the elevation of mitochondrial DNA mutations, were reported at different regions of the central auditory system, such as the inferior colliculus and auditory cortex [154][155][156]. Such high levels of age-related markers of oxidative stress cause a selective loss of the highly energized GABAergic cells as reported in the inferior colliculus [154].…”
Section: The Dilemma Of Inhibitory Downregulation In the Aging Centramentioning
confidence: 99%
“…Additionally, ROS is related to cochlear neuropathy in presbycusis. Evaluated mtDNA oxidative damage and mitochondrial ultrastructural damage in SGNs and auditory cortex were described in aging C57/B6j mice [60]. To mimic human's presbycusis, a senescence-accelerated mouse prone 8 (SAMP8) mouse model was chosen to study the mechanism of ARHL.…”
Section: Redox Homeostasis and Energetic Metabolism Inmentioning
confidence: 99%